Multiple Case Study: Cognitive Status in Pre-Elderly Patients Undergoing Transurethral Resection of Prostate (TURP) Procedure with Spinal Anesthesia - I Made Ghana Astamurti Kumara; Made Rismawan; I Wayan Agus Maharyawan (GLOBAL HEALTH SCIENCE GROUP, 2024)
Benign Prostatic Hyperplasia(BPH) in pre-elderly often causes problems such as discomfort when urinating. The action that can be taken is to perform Transurethral Resection of Prostate (TURP) surgery with Spinal Anesthesia technique. The risks that can occur are Postoperative Cognitive Dysfunction (POCD), such as decreased cognitive function, memory impairment and decreased attention that can occur within a certain period of time. Objective: To determine the cognitive status in pre-elderly patients who underwent TURP procedure with spinal anesthesia. The design of this study was a Multiple Case Study with a qualitative descriptive approach of 5 pre-elderly patient participants who underwent spinal anesthesia. The data collection tools used in this study are interview sheets and MMSE (Mini-Mental State Examination) observation sheets which are used to enter patient observation. Results of the five participants, only two experienced moderate cognitive status disorders and three participants did not experience post-operative cognitive status disorders. Age is a factor in the occurrence of post-operative cognitive status disorders. Two of the five participants in this study experienced moderate cognitive status disorders.